Analisis Faktor-faktor yang Mempengaruhi Loyalitas Konsumen dengan Variabel Intervening Kepuasan Konsumen di Pizza Hut Kota Pamekasan - Septiana, Aldila; Dawam, Aulia; Tarman, Manah (Universitas Pendidikan Ganesha, 2023)
With the expansion of the Pizza Hut business in big cities, it tries to expand its business network. One way is to open a branch in Pamekasan City with district scope, which targets the middle to lower economic community. The purpose of this study was to see and analyze the effect of price, service quality, and atmosphere simultaneously influencing consumer loyalty with the intervening variable of customer satisfaction at Pizza Hut, Pamekasan City. The results showed that there was a significant influence of price, service quality, and atmosphere variables on loyalty through customer satisfaction. This can be seen from the results of the F test on the variables of price, service quality, and atmosphere on loyalty through customer satisfaction, it is obtained an F table of 4.18 < F count of 12.947, so Ho is rejected and Ha is accepted. In particular, the price also adjusts to the purchasing power of the people belonging to the district level. The quality of service provided by Pizza Hut in Pamekasan City can be said to be good, but it must also pay attention to local wisdom and be sustainable (recruiting local human resources in Pamekasan Regency).